Treating the dead; how far ought medicine go to obtain transplantable organs? - Bernstock, Joshua D.; Chalif, Joshua I.; Jha, Rohan; Brown, Ashley; Essayed, Walid I.; Caplan, Arthur; Peruzzi, Pierpaolo (Frontiers in Transplantation, 2023)
Under what circumstances, is it ethical to perform tumor surgery on a brain-dead individual? The neurosurgeons at Brigham and Women's Hospital were recently faced with such a question when asked to operate on a 28-year-old man who was pronounced brain-dead secondary to a severe brain-stem injury. His advanced directives clearly documented a desire for organ donation. During his transplant work-up, cranial imaging suggested a possible cerebellar mass of unknown etiology that was concerning for metastatic disease. Despite negative full body imaging, the neurosurgical team was asked to perform an open biopsy of the intracranial lesion to rule out occult systemic cancer. This case invites many nuanced questions related to the decisions surgeons and the broader medical community must make in the face of pursuing viable organs for the many in need. What is the moral standing and personhood eligibility of brain-dead individuals? What is the scope of medical interventions and procedures that surgeons are ethically bound to carry out? How ought the desire for increased medical intervention to try to save organs be balanced with practical limitations given limited medical resources?